Pandangan Islam terhadap Penggunaan Ventilator dalam Penanganan Kondisi Kritis Pasien - Khalishah Hanif Ervindra; Dzakira Latifa Az-Zahra; Rifdah Buya Harmaidah (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2024)
The role of ventilators as life-support devices in critical care has prompted ethical and religious discussions within Islamic perspectives, particularly regarding end-of-life decisions. Islam mandates the preservation of life as a sacred duty under the principle of hifz an-nafs (protection of life), balanced with the prohibition of excessive measures (israf) and avoidance of unnecessary suffering (la darar wa la dirar). This study explores Islamic perspectives on the use of ventilators by integrating modern medical ethics with Islamic jurisprudence, aiming to provide nuanced guidance for healthcare providers and Muslim families. Employing a qualitative document analysis, this research examines fatwas from various Islamic institutions and relevant ethical theories in Islamic law. Findings indicate significant variability among Islamic rulings, where some permit the withdrawal of ventilators under specific medical prognoses, while others advocate continued use as long as signs of life persist. The study underscores the need for comprehensive, practical Islamic medical guidelines to support healthcare providers and patients' families in making informed, ethical decisions in critical care situations.